3-D STATIC RESERVOIR MODELLING AND HYDROCARBON ESTIMATION IN AF FIELD, TARAKAN BASIN, NORTH KALIMANTAN - Sari Fani, Audini
AF field is located in Tarakan Basin, Berau Sub-Basin, North Kalimantan. This study focused on Mangkabua formation as a gas reservoir. The purpose of this study is to learn about the geological condition, build reservoir static modelling, and estimate hydrocarbons in the AF field. This research uses three wells data and seismic 2-D with total track ±208 km. Three wells are; wireline log, lithology description, side well core, and biostratigraphy. Several methods used in this study are; wells data analysis form determining reservoir intervals, correlation between wells and depositional environment analysis, and petrophysics analysis. Integration of seismic and wells data to create time and depth structure maps, three-dimensional structure modelling, facies modelling and petrophysics modelling, determination of fluid contact and hydrocarbon volume estimation. Geologic structure found in this study faults consist of NW-SE associated with anticline, interpreted as strike-slip fault and faults consist of NE-SW. Based on depositional analysis showed this interval deposited in deep marine in the form of incised channel, channel levee complex and lobe. Hydrocarbon in this area study are gas trapped in an anticline structure trending NW-SE. Estimates of hydrocarbon volume in place (OGIP) in Reservoir A are 32,5 BSCF, and in Reservoir B are 19,7 BSCF.